Effect of different form of upper limb muscles training on dyspnea in chronic obstructive pulmonary disease: A study protocol. Issue 38 (18th September 2020) - Beaumont, Marc; Péran, Loic; Berriet, Anne Cécile; Le Ber, Catherine; Le Mevel, Patricia; Courtois-Communier, Emmanuelle; Couturaud, Francis
Abstract: Introduction: In activities involving upper limbs, patients with chronic obstructive pulmonary disease (COPD) report an increase in dyspnea. For this reason, the authors of the recommendations about pulmonary rehabilitation propose to perform upper limbs muscle strengthening in patients with COPD. However, the modalities of strengthening are not clearly established. The aim of this study is to compare the effects of upper limbs endurance strengthening versus upper limbs force strengthening, in patients with COPD during a pulmonary rehabilitation program. Methods: This study is a randomized, open-label, bi-center controlled trial in parallel groups distributed in a ratio (1:1) comparing upper limbs force strengthening (group F) to the upper limbs endurance strengthening (group E) during a pulmonary rehabilitation program in patients with COPD stages 2 to 4 (A–D). After randomization, patients will be allocated to follow:  A 4 weeks pulmonary rehabilitation program with upper limbs resistance strengthening (group F).  A 4 weeks pulmonary rehabilitation program with upper limbs endurance strengthening (group E). The primary outcome is dyspnea measured with the London Chest Activity of daily Living questionnaire. The secondary outcomes are dyspnea (using Modified Medical Research Council dyspnea Scale, dyspnea-12 questionnaire, multidimensional dyspnea profile questionnaire), upper limb exercise capacity (using the 6-minute Peg Board and Ring Test), Maximal voluntary strength of deltoid, biceps, and brachial triceps. The sample size calculated is 140 patients per group, or 280 in total. Discussion: The modalities of upper limb strengthening are not very well known, and evidence based is lacking to recommend endurance or resistance upper limb strengthening. We anticipate that the results of this study will be of relevance to clinical practice. They will bring information about the best modality of upper limb strengthening to use during a pulmonary rehabilitation program. Trial registration: IdRCB n°2018-A00955-50; V1.1 du 11/07/2018; REHABSUP, clinical trial.gov (NCT03611036), registered August 02, 2018, https://clinicaltrials.gov/ct2/show/NCT03611036 . Abstract : Supplemental Digital Content is available in the text